Towards a participatory smart city: a closer look at smart city endeavors in Berlim and Lisboa - Kremsreiter, Katharina Johanna (2017)
Much literature is dealing unilaterally with technology as the main success factor of the Smart City. Towards a Participatory Smart City aims at looking at human and managerial factors. By elucidat-ing the citizens’ as well as city governments’ perspective through a survey and expert interviews, the requirements for a participatory Smart City are highlighted. As policies based on citizen in-volvement are more widely accepted, this thesis contends that a participatory Smart City will be a more widely adopted and successful one. Finally, a framework for such a participatory Smart City is given, integrating people, technology, and city government meaningfully.